2013
DOI: 10.3171/2013.4.jns121189
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Schwann cells in a collagen tube for the repair of large, segmental peripheral nerve defects in rats

Abstract: Object Segmental nerve defects pose a daunting clinical challenge, as peripheral nerve injury studies have established that there is a critical nerve gap length for which the distance cannot be successfully bridged with current techniques. Construction of a neural prosthesis filled with Schwann cells (SCs) could provide an alternative treatment to successfully repair these long segmental gaps in the peripheral nervous system. The object of this study was to evaluate the ability of autologous SCs to increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 85 publications
4
69
0
3
Order By: Relevance
“…1,6,7,9,11,12,16,17,27,28,34,37,38,[40][41][42]44 Berrocal et al demonstrated that adding autologous SCs suspended in serum to AGCs significantly enhanced the ability to bridge larger gap distances in sciatic nerve repair in rats. 3 Autologous SCs can be harvested from either a donor nerve or from the epicenter of the traumatized nerve ends in sharp injuries (propeller injury, gunshot wound, stab wound). Harvesting SCs from donor nerves requires sacrifice of sensory donor nerves, which may lead to future morbidity, whereas harvesting from the traumatized nerve ends will lead to no deficit because these ends will eventually scar and be sacrificed by the surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,7,9,11,12,16,17,27,28,34,37,38,[40][41][42]44 Berrocal et al demonstrated that adding autologous SCs suspended in serum to AGCs significantly enhanced the ability to bridge larger gap distances in sciatic nerve repair in rats. 3 Autologous SCs can be harvested from either a donor nerve or from the epicenter of the traumatized nerve ends in sharp injuries (propeller injury, gunshot wound, stab wound). Harvesting SCs from donor nerves requires sacrifice of sensory donor nerves, which may lead to future morbidity, whereas harvesting from the traumatized nerve ends will lead to no deficit because these ends will eventually scar and be sacrificed by the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…10,14,15,19,21,23,24,30,31 After this foundation was laid, several studies have shown the ability of SCs to enhance axonal regeneration and improve functional recovery in peripheral nerve injury in mice, rats, and nonhuman primates. 3,20,24,25,34 In this report we present 2 long-segment (7.5-and 5-cm) sciatic nerve injuries where SCs were combined with an autologous nerve construct. These are the first 2 cases in which autologous SCs were transplanted into peripheral nerve injuries in humans (Table 1).…”
mentioning
confidence: 99%
“…The rate of axon regeneration across 15 mm rat sciatic nerve gaps is faster if macrophages with a pro-healing (M2a and M2c phenotype) vs. pro-inflammatory phenotype are combined with polymeric nerve tubes [329]. This can be accomplished by the local delivery of either Interferon-gamma (IFN-gamma) or Interleukin-4 (IL-4), within the tubes [329].…”
Section: Macrophagesmentioning
confidence: 99%
“…This can be accomplished by the local delivery of either Interferon-gamma (IFN-gamma) or Interleukin-4 (IL-4), within the tubes [329]. The neuron-macrophage interactions involved in eliciting a pro-regenerative phenotype in macrophages may be a novel target to induce long-lasting regenerative processes after axonal injuries in the CNS [327].…”
Section: Macrophagesmentioning
confidence: 99%
“…2,13 In addition to restoring motor and/or sensory function, nerve repair can mitigate and/or reduce the incidence and severity of neuroma formation and subsequent development of neuropathic pain. 5 With recent advances in surgical technique and the use of tendon transfers, patients can expect better functional outcomes than ever before. 2 When the damage to the sciatic nerve is extensive enough to preclude coaptation, nerve grafting techniques with autologous sensory nerve graft are used.…”
mentioning
confidence: 99%